Can a temporary financial assistance scheme prevent a transition into poverty among individuals who experienced a life event crisis?. Issue 1 (2nd January 2018) - Kim, Chang-O
Abstract : This article evaluates the impact of the Crisis Assistance Program for Basic Living (CAPBL), which was implemented in South Korea to assist at-risk individuals by providing temporary benefits. National administration data for 30, 845 individuals covering 2009 to 2011 were analyzed to compare poverty transition time in recipients vs. non-recipients using a quasi-experimental design. The results indicate that the CAPBL did not prevent at-risk individuals from transitioning into poverty but, instead, facilitated individuals' transition into welfare recipients. The findings suggest that the program must be fundamentally reformed to prevent individuals from being trapped in poverty.